How the South Joined the Gambling Nation : The Politics of State Policy Innovation - Nelson, Michael, 1949- (Book collections on Project MUSE., 2007)
A national map of legalized gambling from 1963 would show one state, Nevada, with casino gambling and no states with lotteries. Today's map shows eleven commercial casino states, most of them along the Mississippi River, forty-two states with state-owned lotteries, and racetrack betting, slot-machine parlors, charitable bingo, and Native American gambling halls flourishing throughout the nation. For the past twenty years, the South has wrestled with gambling issues. In How the South Joined the Gambling Nation, Michael Nelson and John Lyman Mason examine how modern southern state governments ha.